(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Going to work during the COVID-19 pandemic has placed frontline workers under immense and unprecedented pressures, putting their physical, mental, and social well-being at risk. Staff under excessive or prolonged stress become more prone to frequent absences from work or reduced productivity while at work, accidents, and mistakes. In the COVID-19 pandemic, this may mean compromised quality and safety of care, breach of protocols and guidelines, increased risk of infections, and compromised capacity of the health system and emergency response teams to fight the pandemic. While frontline workers have the responsibility of caring for themselves and verbalizing their needs and concerns, many of the efforts to prevent and reduce stress and care for the mental health of frontline workers must be made by organizations, managers, and health administrators.